2018
DOI: 10.2478/macvetrev-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Еffect of Season and Parity on the Reproductive Performance of Sows

Abstract: The aim of this study was to analyze the effect of season and number of parity on the reproductive performance of sows kept on a commercial farm. To achieve this objective, 800 nrs productive parent sows and a total of 958 parities were analyzed. The results show that sow’s breeding season had a significant effect on the weaning-to-oestrus interval, the farrowing rate, the litter size and weaning piglets with positive results during autumn, winter and spring seasons. The number of parity has a significant effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
3
Order By: Relevance
“…Table 8 lists the main conclusions of some studies on the effect of light time on milk yield and weight loss of multiparous sows. The results showed that there was no significant difference in prolactin concentration, milk composition and colostrum intake of multiparous sows under the light time of 8, 16 and 23 h during lactation, but their feed intake and weight loss were reduced under the light time of 16 and 23 h (Dimitrov et al, 2018; Lachance et al, 2010; Liu, Braden, et al, 2021; Liu, Song, et al, 2021; Mabry et al, 1982). Meanwhile, the lactation number of multiparous sows, as well as the number and weight of weaned piglets under 16 h light were more than those under 8 h light (Kraeling et al, 1987; McGlone, Stansbury, & Tribble, 1988; McGlone, Stansbury, Tribble, & Morrow, 1988; Sevillano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 8 lists the main conclusions of some studies on the effect of light time on milk yield and weight loss of multiparous sows. The results showed that there was no significant difference in prolactin concentration, milk composition and colostrum intake of multiparous sows under the light time of 8, 16 and 23 h during lactation, but their feed intake and weight loss were reduced under the light time of 16 and 23 h (Dimitrov et al, 2018; Lachance et al, 2010; Liu, Braden, et al, 2021; Liu, Song, et al, 2021; Mabry et al, 1982). Meanwhile, the lactation number of multiparous sows, as well as the number and weight of weaned piglets under 16 h light were more than those under 8 h light (Kraeling et al, 1987; McGlone, Stansbury, & Tribble, 1988; McGlone, Stansbury, Tribble, & Morrow, 1988; Sevillano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the litter size, prolactin concentration, milk composition and colostrum intake of lactating sows under different light times Liu, Song, et al (2021) The weight loss of lactating sows under 8 h light was higher than that of lactating sows under 16 h light Dimitrov et al (2018) The weight loss of sows during lactation in July were higher than that in January Kraeling et al (1987) The litter rate of sows was reduced with the decrease of sunlight in autumn Sevillano et al (2016) The milk yield and litter size of sows were significantly increased under the light-dark cycles of 16:8…”
Section: Lachance Et Al (2010)mentioning
confidence: 90%
“…Los resultados obtenidos fueron superiores a lo señalado por Dimitrov et al (2018) quienes Moreno et al Research 2(2), 54-59, 2020 Figura 1 Variación del porcentaje de lechones nacidos vivos según el número de parto Estación y número de parto en el rendimiento de la Camborough 29 Research 2(2), 54-59, 2020 encontraron el máximo valor al tercer parto 13,44, utilizando marranas de la línea TOPIGS. Sevillano ( 2009) reportó en Camborough 22 que en el cuarto parto se obtiene el máximo valor con 13,5 lechones nacidos vivos.…”
Section: Resultados Y Discusiónunclassified
“…Estos resultados concuerdan con lo reportado por Dimitrov et al (2018) en marranas de la Figura 2 Variación del porcentaje de lechones nacidos muertos según el número de parto línea TOPICS quienes obtuvieron un mayor % LNM en el cuarto y quinto parto (8,26 y 8,19, respectivamente). Olson et al (2018) señalan dos motivos que explicarían estos resultados, el primero se relaciona con la habilidad materna que decrece conforme aumenta el número de parto, las marranas aumentan de peso, son más torpes y tienen más problemas de salud en el aparato locomotor y daños en los pezones, el segundo motivo puntualiza que las marranas más viejas tuvieron camadas más grandes y lechones con bajos pesos.…”
Section: Peruvian Agriculturalunclassified
See 1 more Smart Citation